BASKETBOLDA TOP HAKİMİYETİNİN ANALİZİ VE TAKIM PERFORMANSI ÜZERİNE ETKİSİ - Ural Gökay ÇİÇEKLİ; Murat KOCAMAZ; Haluk SOYUER (Pamukkale University, 2012)
Basketball is one the most popular sport in Turkey. In recent years, there are increasing number of papers in literature for understanding the effect of team performance by using statistical models for basketball. The aim of this study is to understand the true nature of the performance in "Türkiye - Beko Basketbol Ligi"between 2010 and 2011 by using the possession and 4F analysis for each teams. Furthermore this study represents a pre-study for future papers to develop statistical methods which will be used in basketball.